Enhancing agency and empowerment in agricultural development projects: A synthesis of mixed methods impact evaluations from the Gender, Agriculture, and Assets Project, Phase 2 (GAAP2) - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Malapit, Hazel J.; Seymour, Greg; Heckert, Jessica; Doss, Cheryl; Johnson, Nancy L.; Rubin, Deborah; Ramani, Gayathri V.; Myers, Emily; van Biljon, Chloe; Mulema, Annet; et al. (Elsevier, 2024)
Development interventions increasingly include women’s empowerment and gender equality among their objectives, but evaluating their impact has been stymied by the lack of measures that are comparable across interventions. This paper synthesizes the findings of 11 mixed-methods impact evaluations of agricultural development projects from South Asia and sub-Saharan Africa that were part of the Gender, Agriculture, and Assets Project, Phase 2 (GAAP2). As part of GAAP2, qualitative and quantitative data were used to develop and validate the multidimensional project-level Women’s Empowerment in Agriculture Index (pro-WEAI), which was used to assess the impact of GAAP2 projects on women’s empowerment. This paper assesses the extent to which: (1) a two- to three-year agricultural development project can contribute to women’s empowerment; and (2) a suite of methods comprising a standardized quantitative measure of women’s empowerment and a set of qualitative protocols, can evaluate such impacts. Our synthesis finds that the most common positive significant impacts were on the instrumental and collective agency indicators that comprise pro-WEAI, owing to the group-based approaches used. We found few projects significantly improved intrinsic agency, even among those with explicitly stated objectives to change gender norms. Unsurprisingly, we find mixed, and mostly null impacts on aggregate pro-WEAI, with positive impacts more likely in the South Asian, rather than African, cases. Our results highlight the need for projects to design their strategies specifically for empowerment, rather than assume that projects aiming to reach and benefit women automatically empower them. Our study also shows the value of a suite of methods containing a common metric to compare empowerment impacts and qualitative protocols to understand and contextualize these impacts.